2017
DOI: 10.1111/bph.14036
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside/nucleotide reverse transcriptase inhibitors attenuate angiogenesis and lymphangiogenesis by impairing receptor tyrosine kinases signalling in endothelial cells

Abstract: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 81 publications
(97 reference statements)
1
15
0
Order By: Relevance
“…Lamivudine attenuated laser-induced choroidal neovascularization in mice (Mizutani et al, 2015. A recent study also revealed that lamivudine and tenofovir inhibit VEGFR-2 phosphorylation in VEGF-stimulated human dermal microvascular endothelial cells (Song et al, 2018). In this study, compatible with the previous studies, the VEGFR-2 phosphorylation was significantly downregulated in NUCs-treated Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lamivudine attenuated laser-induced choroidal neovascularization in mice (Mizutani et al, 2015. A recent study also revealed that lamivudine and tenofovir inhibit VEGFR-2 phosphorylation in VEGF-stimulated human dermal microvascular endothelial cells (Song et al, 2018). In this study, compatible with the previous studies, the VEGFR-2 phosphorylation was significantly downregulated in NUCs-treated Fig.…”
Section: Discussionsupporting
confidence: 91%
“…It is thought that the NUCs attenuate liver cirrhosis by suppressing HBVrelated liver damage. However, NUCs have been known to exert effects other than viral suppression, such as NO production (Zídek et al, 1999;Kostecká et al, 2012) and angiogenesis (Mizutani et al, 2015;Song et al, 2018). This study, therefore, assessed the therapeutic potential of NUCs on nonviral cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-reverse transcriptase inhibitors zidovudine and lamivudine can downregulate MMP-9 expression in normal or tumor cells, weaken MAPK/ERK or PI3K/AKT phosphorylation, reduce nitric oxide production and impair angiogenesis [ 174 , 216 , 217 , 218 ]. In contrast, other HIV-reverse transcriptase inhibitors (e.g., tenofovir and efavirenz) are able to exert either pro- or anti- tumor activities [ 217 , 219 ].…”
Section: Mmp-9 Inhibitorsmentioning
confidence: 99%
“…DAPI staining was used to assess the positions of the nuclei after staining for 10 min at 37°C. Finally, the red fluorescence intensity was measured under an FV1000 Olympus confocal microscope (Olympus) at excitation/emission wavelengths of 510 nm/580 nm (Song et al ., ).…”
Section: Methodsmentioning
confidence: 97%